Clarification and 3-D visualization of immunolabeled human placenta villi. (May 2017) - Merz, George; Schwenk, Valerie; Shah, Ruchit G.; Necaise, Phillip; Salafia, Carolyn M.
Abstract: We report here the successful 3D visualization of human placenta villous structures on the order of ∼1 mm 3 by a combination of immunolabeling, rapid tissue clarification and laser scanning confocal microscopy. The resultant image sets exhibit a complex arrangement of villi and their contained vasculature that mirrors their arrangement in situ . Highlights: A rapid and simplified method to immunolabel and clarify placental tissue. Successful confocal microscopic imaging of large volumes (∼1 mm 3 ) of villus trees. 3D visualization of villi and their capillaries across gestational ages.